REKONSTRUKSI SYURA SEBAGAI MODEL RESOLUSI KONFLIK BERBASIS KEADILAN RESTORATIF DALAM PERSPEKTIF HUKUM ISLAM - Fakri (STAI Nusantara Kota Banda Aceh, 2026)
Conflict is an inevitable aspect of social life and requires a dispute resolution mechanism that not only ensures legal certainty but also restores social relationships among the parties involved. In practice, dispute resolution remains predominantly retributive, emphasizing punishment rather than addressing the needs of victims, offenders, and the wider community. This study aims to analyze the concept and principles of shūrā in Islamic law, examine its relevance to restorative justice, and reconstruct shūrā as a restorative conflict resolution model. This research employs normative legal research using statutory, conceptual, and philosophical approaches. The data were collected through library research involving the Qur'an, Hadith, classical and contemporary Islamic legal literature, legislation, and relevant scholarly publications. The data were analyzed using descriptive-analytical, deductive, and comparative-conceptual methods. The findings reveal that shūrā shares substantial compatibility with restorative justice principles, particularly in promoting dialogue, participation, accountability, protection of affected parties, and restoration of social harmony. The novelty of this study lies in reconstructing shūrā into a restorative conflict resolution model consisting of seven stages: conflict identification, establishment of a restorative shūrā forum, dialogue and fact-finding, formulation of restorative measures, mutual agreement, implementation and monitoring, and social reintegration. This model extends the function of shūrā beyond a consultative decision-making mechanism into a systematic and justice-oriented conflict resolution framework grounded in Islamic legal values and responsive to contemporary societal needs.